An Overview on Applications of Microcontroller (International Journal of Innovative Research in Engineering & Management, 2021)
A microcontroller is a microcomputer's electronic gadget. VLSI technology is used to create them on an one circuit.  Computers with term durations varying from 4 to 8 parts, 64  parts to 128 bits are now available. This chapter covers  controller, their construction, and a variety of properties.  Choosing a microcontroller for a given application is very  challenging. The success or failure of any project is mainly  determined by the microcontroller unit used. In this article, a  short review of the unit is given in terms of making the best  choice for a certain application. Many companies produce  microcontrollers in large quantities. The evaluation is focused  on the products of a few well-known firms. System needs,  efficiency, size, energy consumption, adaptability,  dependability, durability, atmospheric limitations, application  support, accuracy, security, price, and the experience and  prior records of the manufacture are all factors to consider all  important considerations when using a microcontroller as the  device's heart. Several variables are highlighted in this article,  and following through on those aspects leads to project  success.
Keywords: Applications; Bit; CISC; Microcontroller; RISC